2021
DOI: 10.1021/acsomega.1c00935
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated Nonsaccharide Heparin Mimetics Are Potent and Noncompetitive Inhibitors of Human Neutrophil Elastase

Abstract: Human neutrophil elastase (HNE) is a serine protease that plays vital roles in inflammation, innate immune response, and tissue remodeling processes. HNE has been actively pursued as a drug target, particularly for the treatment of cardiopulmonary diseases. Although thousands of molecules have been reported to inhibit HNE, yet very few are being evaluated in early clinical trials, with sivelestat as the only approved HNE inhibitor. We report here a novel chemotype of sulfonated nonsaccharide heparin mimetics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 69 publications
0
33
0
Order By: Relevance
“…We also evaluated LSAS inhibitory potential against other proteases including plasmin, trypsin, chymotrypsin, human neutrophil elastase (HNE), and cathepsin G using the corresponding chromogenic substrate hydrolysis assays under near physiologic conditions, as reported in our earlier studies [ 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 ]. In these assays, the inhibition potential was determined by spectrophotometric measurement of the residual protease activity in the presence of varying concentrations of LSAS ( Figure 3 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also evaluated LSAS inhibitory potential against other proteases including plasmin, trypsin, chymotrypsin, human neutrophil elastase (HNE), and cathepsin G using the corresponding chromogenic substrate hydrolysis assays under near physiologic conditions, as reported in our earlier studies [ 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 ]. In these assays, the inhibition potential was determined by spectrophotometric measurement of the residual protease activity in the presence of varying concentrations of LSAS ( Figure 3 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, targeting FXI(a)/FXII(a) axis by therapeutic tools has been demonstrated to prevent systemic inflammation, coagulopathy, and mortality in experimental sepsis [ 40 , 41 ]. Interestingly, we found in this study that LSAS inhibits HNE, an inflammatory serine protease the overactivity of which contributes to a host of cardiopulmonary diseases [ 13 ], with an IC 50 value of 4.7 ± 0.2 µg/mL ( Table 2 ). Furthermore, we also found that LSAS inhibits another inflammatory protease, i.e., cathepsin G [ 42 ] with an IC 50 value of 0.73 ± 0.11 µg/mL ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules 1 – 5 and 11 were obtained from Sigma‐Aldrich and Fisher Scientific. Other molecules were obtained following modified reported synthetic protocols (Al‐Horani et al, 2021; Kassack et al, 2004; McCain et al, 2004; Trapp et al, 2007). For instance, the pure sodium salts were produced by SP Sephadex‐Na cation exchange chromatography and then by Sephadex G10 size exclusion chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition potential of several sulfonated molecules against thrombin, FXa, FIXa, plasmin, trypsin, chymotrypsin, cathepsin G, HNE, and proteinase 3 was also investigated using previously reported chromogenic substrate hydrolysis assays (Al‐Horani, Abdelfadiel, et al, 2019; Al‐Horani, Clemons, et al, 2019; Al‐Horani et al, 2015, 2021; Kar et al, 2020, 2021). For example, to each well of a 96‐well microplate containing 85 μl or 185 μl of 20–50 mM Tris‐HCl buffer, pH 7.4, containing 100–150 mM NaCl, 0.1% PEG8000, and 0.02% Tween80 at either 25°C or 37°C was added 5 μl of the inhibitor (or high pure water) and 5 μl of the enzyme.…”
Section: Methodsmentioning
confidence: 99%